(untitled) (Orfeu, 2022)
Seeking to know how the (auto)biographical research are being developed in music education, we analyzed 47 theses and dissertations throughout a state of knowledge study. We highlight the analysis of the theoretical framework, methodology and neologisms constituted at the interface between music education and (auto)biography. These works reinforce the autonomy of music education as an area of knowledge, and even face to the contribution of sociology, psychology and philosophy, their objects of study focus on specific issues and empirical fields of music education. The methodology of the studies reveals a plurality of names used that merge with terms of research’ approaches: narratives, biographical, life stories, oral history, although we perceive few variations between authors to substantiate. We found six new terms with concepts outlined by the researchers, which contribute to the vocabulary of music education’ area, showing the conceptual crossroads of the area and expanding the investigative paths taken.